Glucose - Responsive Smart Insulin - Krishnamurthy, Aishwarya; Goswami, Ravinder (Annals of the National Academy of Medical Sciences (India), 2018)
The discovery of insulin in 1920s revolutionized the management of Type 1 Diabetes Mellitus. The evolution of insulin over the last nine decades has seen three phases, namely discovery and understanding of the molecule, advances in synthesis of the molecule and advancements in the optimization of insulin structure and delivery. These advances aim to minimize hypoglycemia while simultaneously improving anti-hyperglycemic efﬁcacy. Glucose-responsive insulin (GRI) systems were ﬁrst conceptualized in 1979. These are novel insulin formulations that provide anti hyperglycemic activity appropriate to circulating glucose levels but with a mechanism to avoid hypoglycemia, that often accompanies stringent glycemic control. GRIs are of three major typesalgorithm-based mechanical, polymer-based, molecular GRI analog systems. They differ in the mechanisms of achieving glucose responsiveness. Algorithm-based systems are closed loop insulin pumps that adjust insulin delivery commensurate with blood glucose levels on the basis of predetermined algorithms, that terminate or increase insulin delivery according to blood glucose trends. The second category of GRI includes glucose-responsive polymer-based matrices that house insulin, releasing insulin as needed based on ambient glucose levels. The third approach is to incorporate glucose sensitive motifs in the insulin molecule itself that would decrease or increase insulin availability based on blood glucose levels. The mechanisms behind these novel approaches to insulin delivery and action will be the focus of this review article.